![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
Let$f(x)$ be a polynomial with positive degree satisfying the relation $f(x)f(y)=f(x)+f(y)+f(xy)-2$
For all real x and y. Suppose$f(4)=65$ Then
(A) ${{f}^{'}}(x)$ is a polynomial of degree two
(B) roots of equation ${{f}^{'}}(x)=2x+1$ are real
(C) $x{{f}^{'}}(x)=3\left[ f(x)-1 \right]$
(D) ${{f}^{'}}(-1)=3$
Answer
125.1k+ views
Hint: First convert the equation in one form and assume$y=\dfrac{1}{x}$and solve it further.
Complete step-by-step answer:
Let $f(x)$ is a polynomial satisfying,
$f(x)f(y)=f(x)+f(y)+f(xy)-2$…….. (1)
Now Let us consider $y=\dfrac{1}{x}$…….(2)
Now let us substitute (2) in (1) we get,
$f(x)f\left( \dfrac{1}{x} \right)=f(x)+f\left( \dfrac{1}{x} \right)+f(1)-2$……….. (3)
Let us take $x=1$ So substituting the value of $x$ in (3),
So we get ,
$\Rightarrow$ $f{{(1)}^{2}}=3f(1)-2$
Simplifying we get,
$\begin{align}
& f{{(1)}^{2}}-3f(1)+2=0 \\
& f{{(1)}^{2}}-2f(1)-f(1)+2=0 \\
& f(1)(f(1)-2)-(f(1)-2)=0 \\
& (f(1)-1)(f(1)-2)=0 \\
\end{align}$
So by solving we get two values for$f(1)$,
So the values for$f(1)$ are as follows,
$f(1)=1,2$…………… (4)
Let us take $y=1$and substituting in (1),
So we get,
$\Rightarrow$ $f(x)f(1)=f(x)+f(1)+f(x)-2$
$\Rightarrow$ $f(x)f(1)=2f(x)+f(1)-2$
So rearranging the equation we get,
$\Rightarrow$ $(f(x)-1)(f(1)-2)=0$
So here $f(x)\ne 1$ and we can say that$f(1)=2$…………..(5)
So from equation (4) and (5) we get to know that $f(1)=2$,
So substituting $f(1)=2$in (3) we get,
So we get,
$\Rightarrow$ $f(x)f\left( \dfrac{1}{x} \right)=f(x)+f\left( \dfrac{1}{x} \right)+2-2$
$\Rightarrow$ $f(x)f\left( \dfrac{1}{x} \right)=f(x)+f\left( \dfrac{1}{x} \right)$
So $f(x)$ is a polynomial function, let us consider it as,
$\Rightarrow$ $f(x)=\pm {{x}^{n}}+1$
$\Rightarrow$ $f(4)=\pm {{4}^{n}}+1=65$………….( Given in question that $f(4)=65$)
$\begin{align}
& \pm {{4}^{n}}=64 \\
& \pm {{4}^{n}}={{4}^{3}} \\
\end{align}$……………… (as we know${{4}^{3}}=64$so writing${{4}^{3}}$instead of$64$)
So we get the value of $n$ as $3$,
So we get$f(x)$as,
$f(x)={{x}^{3}}+1$
So differentiating $f(x)$ We get,
So we get${{f}^{'}}(x)$as,
${{f}^{'}}(x)=3{{x}^{2}}$
So considering option (A),
${{f}^{'}}(x)=3{{x}^{2}}$
So it has a polynomial of degree two. Option (A) is correct,
Now for option (B) it is mentioned that${{f}^{'}}(x)$ is Real ,
So${{f}^{'}}(x)=3{{x}^{2}}$ so it is real, if we put any value we will get ${{f}^{'}}(x)$as real.
So option (B) is correct.
Now considering Option (C) We get
$x{{f}^{'}}(x)=3\left[ f(x)-1 \right]$
Let us take $x=1$
We get LHS$=$RHS
Option (C) is also correct.
For Option (D) it is given that${{f}^{'}}(-1)=3$
So we have found${{f}^{'}}(x)$above
So${{f}^{'}}(x)=3{{x}^{2}}$
So Substituting $x=-1$ in${{f}^{'}}(x)$ We get,
${{f}^{'}}(-1)=3$
Hence Option (D) is also correct.
So here all options are correct.
Option (A), (B), (C) and (D) are correct.
Note: While solving be careful of what you are supposed to substitute. Also don’t jumble yourself and use proper signs and assumptions. Use the polynomial as given in question. Use proper substitution as we had used $y=\dfrac{1}{x}$. So be careful about solving all the options and proving it right or wrong. You should not make a mistake at simplifying this one$f(x)=\pm {{x}^{n}}+1$.
Complete step-by-step answer:
Let $f(x)$ is a polynomial satisfying,
$f(x)f(y)=f(x)+f(y)+f(xy)-2$…….. (1)
Now Let us consider $y=\dfrac{1}{x}$…….(2)
Now let us substitute (2) in (1) we get,
$f(x)f\left( \dfrac{1}{x} \right)=f(x)+f\left( \dfrac{1}{x} \right)+f(1)-2$……….. (3)
Let us take $x=1$ So substituting the value of $x$ in (3),
So we get ,
$\Rightarrow$ $f{{(1)}^{2}}=3f(1)-2$
Simplifying we get,
$\begin{align}
& f{{(1)}^{2}}-3f(1)+2=0 \\
& f{{(1)}^{2}}-2f(1)-f(1)+2=0 \\
& f(1)(f(1)-2)-(f(1)-2)=0 \\
& (f(1)-1)(f(1)-2)=0 \\
\end{align}$
So by solving we get two values for$f(1)$,
So the values for$f(1)$ are as follows,
$f(1)=1,2$…………… (4)
Let us take $y=1$and substituting in (1),
So we get,
$\Rightarrow$ $f(x)f(1)=f(x)+f(1)+f(x)-2$
$\Rightarrow$ $f(x)f(1)=2f(x)+f(1)-2$
So rearranging the equation we get,
$\Rightarrow$ $(f(x)-1)(f(1)-2)=0$
So here $f(x)\ne 1$ and we can say that$f(1)=2$…………..(5)
So from equation (4) and (5) we get to know that $f(1)=2$,
So substituting $f(1)=2$in (3) we get,
So we get,
$\Rightarrow$ $f(x)f\left( \dfrac{1}{x} \right)=f(x)+f\left( \dfrac{1}{x} \right)+2-2$
$\Rightarrow$ $f(x)f\left( \dfrac{1}{x} \right)=f(x)+f\left( \dfrac{1}{x} \right)$
So $f(x)$ is a polynomial function, let us consider it as,
$\Rightarrow$ $f(x)=\pm {{x}^{n}}+1$
$\Rightarrow$ $f(4)=\pm {{4}^{n}}+1=65$………….( Given in question that $f(4)=65$)
$\begin{align}
& \pm {{4}^{n}}=64 \\
& \pm {{4}^{n}}={{4}^{3}} \\
\end{align}$……………… (as we know${{4}^{3}}=64$so writing${{4}^{3}}$instead of$64$)
So we get the value of $n$ as $3$,
So we get$f(x)$as,
$f(x)={{x}^{3}}+1$
So differentiating $f(x)$ We get,
So we get${{f}^{'}}(x)$as,
${{f}^{'}}(x)=3{{x}^{2}}$
So considering option (A),
${{f}^{'}}(x)=3{{x}^{2}}$
So it has a polynomial of degree two. Option (A) is correct,
Now for option (B) it is mentioned that${{f}^{'}}(x)$ is Real ,
So${{f}^{'}}(x)=3{{x}^{2}}$ so it is real, if we put any value we will get ${{f}^{'}}(x)$as real.
So option (B) is correct.
Now considering Option (C) We get
$x{{f}^{'}}(x)=3\left[ f(x)-1 \right]$
Let us take $x=1$
We get LHS$=$RHS
Option (C) is also correct.
For Option (D) it is given that${{f}^{'}}(-1)=3$
So we have found${{f}^{'}}(x)$above
So${{f}^{'}}(x)=3{{x}^{2}}$
So Substituting $x=-1$ in${{f}^{'}}(x)$ We get,
${{f}^{'}}(-1)=3$
Hence Option (D) is also correct.
So here all options are correct.
Option (A), (B), (C) and (D) are correct.
Note: While solving be careful of what you are supposed to substitute. Also don’t jumble yourself and use proper signs and assumptions. Use the polynomial as given in question. Use proper substitution as we had used $y=\dfrac{1}{x}$. So be careful about solving all the options and proving it right or wrong. You should not make a mistake at simplifying this one$f(x)=\pm {{x}^{n}}+1$.
Recently Updated Pages
JEE Main 2021 July 20 Shift 2 Question Paper with Answer Key
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Atomic Structure and Chemical Bonding important Concepts and Tips
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Amino Acids and Peptides Important Concepts and Tips for Exam Preparation
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main 2023 (January 30th Shift 2) Maths Question Paper with Answer Key
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main 2022 (July 25th Shift 2) Physics Question Paper with Answer Key
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main 2023 (April 6th Shift 2) Maths Question Paper with Answer Key
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
JEE Main 2025 Session 2: Application Form (Out), Exam Dates (Released), Eligibility & More
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main Exam Marking Scheme: Detailed Breakdown of Marks and Negative Marking
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Learn About Angle Of Deviation In Prism: JEE Main Physics 2025
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main 2025: Conversion of Galvanometer Into Ammeter And Voltmeter in Physics
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main Login 2045: Step-by-Step Instructions and Details
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Other Pages
JEE Advanced Marks vs Ranks 2025: Understanding Category-wise Qualifying Marks and Previous Year Cut-offs
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Ideal and Non-Ideal Solutions Raoult's Law - JEE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Mains 2025 Correction Window Date (Out) – Check Procedure and Fees Here!
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Degree of Dissociation and Its Formula With Solved Example for JEE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
JEE Main 2025: Derivation of Equation of Trajectory in Physics
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Electric Field Due to Uniformly Charged Ring for JEE Main 2025 - Formula and Derivation
![arrow-right](/cdn/images/seo-templates/arrow-right.png)